The Effect of Vitamin D3 on Serum Creatine Phosphokinase Level in Patients with Multiple Trauma: A Pilot Randomized Clinical Trial - Mehran Kouchek; Niloufar Taherpour; Mahya Farasat; Mirmohammad Miri; Sara Salarian; Seyedpouzhia Shojaei; Rezvan Hassanpour; Hossein Amini; Mohammad Sistanizad (Iranian Journal of Medical Sciences)
Background: Multiple trauma can cause an increase in creatine phosphokinase (CPK) and subsequently rhabdomyolysis and acute kidney injury (AKI). This study was designed to evaluate the effect of vitamin D3 on the serum CPK level and the incidence of rhabdomyolysis-induced AKI in patients with multiple trauma.Methods: Patients with serum CPK levels <1000 IU/L were followed as the control 1 group. Subjects with serum CPK levels ≥1000 IU/L were randomly allocated to the control 2 or intervention group at Imam Hossein Medical Center, Tehran, Iran in 2020. Patients in the intervention group received a single dose of vitamin D3 (300,000 units) on the recruitment day. The serum level of CPK was recorded every 3 days for 14 days. Parametric and non-parametric tests were used to compare the CPK values between groups.Results: Forty-six patients, consisting of 16, 15, and 15 in control 1, control 2, and intervention arms of the study were recruited, respectively. Unlike control groups, the significant steadily decreasing trend was seen only in the intervention group (P<0.001). This significant decrease in the intervention arm was observed on days 5 to 7 (P=0.001) and on days 8 to 10 (P<0.001) compared to the baseline.Patients in the intervention group had a lower number of AKI or need for dialysis (P=0.869 and P=0.670 for AKI and dialysis, respectively) than control group 2, although the differences were not significant. Conclusion: The current study revealed that vitamin D3, could prevent the increasing trend of CPK during the first days and accelerate the normalization of CPK in patients with elevated CPK due to multiple trauma.Trial registration number: IRCT20120703010178N23.